1982
DOI: 10.1161/01.atv.2.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal hormone levels in men with coronary artery disease.

Abstract: Plasma concentrations and urinary excretions of various hormones and hormone metabolites were measured In four groups. Group 1 was composed of 13 men with prior myocardial infarction; Group 2 contained 35 clinically normal men; Group 3 consisted of 44 men with normal coronary arteriograms; and Group 4 was composed of 25 men with severe coronary artery disease shown on arteriogram but no Infarction. There were four major findings: Group 1 had significantly higher 24-hour mean plasma concentrations of estrone (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 29 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…Two previous studies measured testosterone in men with and without CAD who had not had an MI; one found the mean level of testosterone low in the men with CAD 29 and one found it normal. 30 It appears that no previous studies have measured testosterone in relation to the degree of CAD in men who had not had an MI.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies measured testosterone in men with and without CAD who had not had an MI; one found the mean level of testosterone low in the men with CAD 29 and one found it normal. 30 It appears that no previous studies have measured testosterone in relation to the degree of CAD in men who had not had an MI.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other groups did not confirm these findings using coronary angiography in two male samples (119,120). Retrospective studies have examined whether myocardial infarction survivors were characterized by reduced DHEA-S levels compared with healthy controls (115,116,118). Two of these studies demonstrated that DHEA-S levels were lower in myocardial infarction survivors compared with healthy controls (115,116), while the third one found the opposite (116).…”
Section: Cardiovascular Diseasementioning
confidence: 97%
“…Several studies have identified plasma DHEA or DHEA-S as being cardioprotective (113)(114)(115)(116)(117)(118). In both men and women, elevated DHEA-S levels were associated with retarded progression of atherosclerosis measured by coronary artery angiography (113), ultrasound carotid wall thickness (117) and pulse wave velocity aorta calcification (114).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…6810 ' 11 In contrast, plasma estrogens are elevated in individuals who have symptoms of CHD without angiographically demonstrable evidence of vascular occlusion. 9 Moreover, individuals with hypergonadotrophic hypergonadism (Klinefelters syndrome, 47 XXY) and plasma estrogen levels at least as high as in men with CHD do not experience death rates greater than that predicted for the general population. 12 Additionally, plasma estradiol levels of cases and controls were identical during longitudinal evaluation of low risk and high risk males who subsequently did or did not develop CHD.…”
mentioning
confidence: 99%
“…12 Additionally, plasma estradiol levels of cases and controls were identical during longitudinal evaluation of low risk and high risk males who subsequently did or did not develop CHD. 13 These latter studies in males indicated that hyperestrogenemia may not be a uniform risk factor for CHD because many hyperestrogenemic individuals 9 ' 12>13 do not experience increased episodes of CHD compared to males with normal plasma estrogen content. Moreover, the suggested protective effect of estrogen in females 1 " 5 as opposed to its apparent absence in males 6 ' 8 ' 10 ' 11 implies complex effects of estrogens in CHD that may be genderspecific.…”
mentioning
confidence: 99%